Time-varying volatility model equipped with regime switching factor: valuation of option price written on energy futures - Leduc, Guillaume (2025)
This paper explores the calculation of European option prices on energy futures using a time-varying volatility model enhanced by a regime switching factor. We develop a semi-analytical method to determine the price of European options on these energy futures, involving the derivation of the characteristic function for the energy futures' dynamics. To determine the parameters of the regime switching model and identify when economic states change, we employ the EM algorithm, utilizing real gas futures price data. We validate our closed-form solution for the option pricing through simulations employing the generalized antithetic variates Monte-Carlo technique. A comprehensive numerical analysis demonstrates the effectiveness of our proposed methodology.